Are you FireWise? notebook - Firewise Community Prevention Partnership, author (Colorado State University. Libraries, 2007)
This publication contains wildfire protection guidelines for protecting homes and property in areas such as the mountains and foothills.
Keywords: fire protection engineering; wildfires; Colorado